Kelimpahan Relatif Artropoda Predator Penghuni Tajuk Tanaman Padi Galur Padi Rakitan Politeknik Negeri Lampung - Lina Budiarti; Jaenudin Kartahadimaja; Miranda Ferwita Sari; Destieka Ahyuni; Ni Siluh Putu Nuryanti, Dulbari (Balai Pelatihan Pertanian Jambi, 2021)
The abundance of predatory arthropods in the rice field ecosystem acts as a biological agent that suppresses pest populations. This study aims to analyze the types of species, individuals, and abundance of predatory arthropods. The research was conducted at the Lampung State Polytechnic Seed Teaching Farm in August-December 2020. The rice plant lines planted by Lampung State Polytechnic were 14 New Type Rice (PTB) lines, namely Pandan Wangi (PW, B1, B2, B3, B4, B7, D2, D3, F3, F4, H1, H4, K, and L2 with 2 and comparable superior varieties namely Ciherang (CH) and Gilirang (Gil)). Rice cultivation is carried out conventionally. Observations of predatory arthropods that inhabit rice canopy were carried out using 3 double swings of insect nets / sweepnets per treatment plot. Insect collection was carried out at 06.00-09.00 WIB then identified in the Food Crops Laboratory II, counting the number of species, number of individuals and relative abundance. The results showed that predatory arthropods that inhabit the canopy of rice plants in several rice plant lines were obtained from the Oxyopidae, Tetragnathidae, Lycosidae, Coenagrionidae, Correidae, Coccinellidae, Chrysomelidae, and Staphylinidae families. The Tetragnathidae and Coenagrionidae families have the highest proportion of species and are found in each rice plant line.